2021
DOI: 10.3920/jiff2020.0110
|View full text |Cite
|
Sign up to set email alerts
|

Substrate as insect feed for bio-mass production

Abstract: Insects are able to convert organic material (i.e. waste and by products) into high-quality biomass, which can be processed into animal feed. Several studies have investigated the influence of growing substrates on the nutritional value of different insect species, particularly black soldier fly larvae and prepupae. This article reviews studies on how insects bioconvert different substrates, the effect of the substrate on the composition of insect meals, and on the development time (time needed to reach the ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 43 publications
0
28
0
1
Order By: Relevance
“…Additionally, the protein content in larvae was higher than in the correspondent substrates, ranging from 1.95 of the control diet to 2.51 of the V75 + B25 diet, according to Pinotti and Ottoboni [ 31 ]. In our trial, substrates containing the highest CP and moisture percentage (control and V100) allowed to obtain BSF larvae with the highest CP level, according to Meneguz et al [ 7 ].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Additionally, the protein content in larvae was higher than in the correspondent substrates, ranging from 1.95 of the control diet to 2.51 of the V75 + B25 diet, according to Pinotti and Ottoboni [ 31 ]. In our trial, substrates containing the highest CP and moisture percentage (control and V100) allowed to obtain BSF larvae with the highest CP level, according to Meneguz et al [ 7 ].…”
Section: Discussionmentioning
confidence: 94%
“…Lalander et al [ 30 ] also reported that high levels of moisture in the substrate reduced the biomass conversion ratio and survival rate of the larvae. However, in our trial, the ventilation applied in the larvae-growing chamber can alleviate the negative effects of high-moisture substrates, according to Pinotti and Ottoboni [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…In theory, the concentration should be approximately twice as high in the larvae as in the substrate, providing the larvae had a direct action on the decay of pathogens, but several, not completely known, factors may influence the contamination of larvae grown on a substrate contaminated by foodborne pathogens. On the whole, the results of this study show that larvae grown on a substrate contaminated by foodborne pathogens have a lower pathogen load than the substrate; the quantification of this difference allows one to predict the final contamination of larvae depending on the initial contamination of the substrate, therefore, suggesting the possibility of classifying the different growth substrates to be used to breed BSF larvae for safety implications [ 36 , 37 ], making this breeding more attractive to the market.…”
Section: Discussionmentioning
confidence: 99%
“…These aspects have stimulated feed researchers and producers to look for innovative and alternative ingredients to feed animals. Ex-food, insects, and seaweeds (algae) are considered interesting alternative protein/energy sources for feed [52] and are expected to be increasingly used around the globe as replacements for conventional nutrient sources.…”
Section: The Future Of Animal Productionmentioning
confidence: 99%